Clinical implication of hypovascular hepatocellular carcinoma studied in 4, 474 patients with solitary tumour equal or less than 3 cm. (28th February 2013) - Takayasu, Kenichi; Arii, Shigeki; Sakamoto, Michiie; Matsuyama, Yutaka; Kudo, Masatoshi; Ichida, Takafumi; Nakashima, Osamu; Matsui, Osamu; Izumi, Namiki; Ku, Yonson; Kokudo, Norihiro; Makuuchi, Masatoshi; et al.
Abstract Background & Aims To clarify the biological behaviour of small hypovascular hepatocellular carcinoma (HCC) because of insufficient evidence even though frequently encountered. Methods The study covered naïve 4, 474 patients who met solitary HCC ≤3 cm (mean, 2.1 cm), histopathologically proven and Child Pugh A or B. Macroscopic vascular invasion and distant metastasis were excluded. The hypovascularity of tumour was defined as hypo‐ or iso‐enhancement in arterial phase of multiple dynamic imaging techniques. Results Of them, 802 (18%) were hypovascular. The ratio of hypovascular HCC decreased as tumour size increased (P < 0.001) and most of them developed to hypervascular type when they grew over 1.5 cm. Hypovascular group showed a significantly higher ratio of well differentiated grade (P < 0.001) and marginally less incidence of microvascular invasion and metastases compared with hypervascular group. The histologic dedifferentiation (less differentiation) developed step‐by‐step as tumour size increased in hyper‐ and even hypovascular group. The des‐γ‐carboxy prothrombin (DCP) value ≥ 300mAU/ml was closely correlated with increase of tumour size in both groups. Logistic regression analysis revealed five variables were independent predictors for hypovascular HCC; tumour size ≤1.5 cm, alpha‐fetoprotein < 200 ng/ml, DCP < 40mAU/ml, well differentiated grade, and positivity for hepatitis C virus antibody. Conclusions Hypovascular HCC was biologically less aggressive and developed with stepwise dedifferentiation and transformation to hypervascular appearance along with tumour growth. These results will help in leading correct diagnosis of small hypovascular tumour and assessing optimal treatment for hypovascular HCC≤3 cm.